A field trial comparing four oral nonsteroidal anti-inflammatory drugs on controlling cautery dehorning pain and stress in calves - Stock, Matthew L (Transl Anim Sci, 2021)
The purpose of this study was to compare the analgesic effect of four nonsteroidal anti-inflammatory drugs (NSAIDs) administered as a single, standardized, oral dose in dairy calves at the time of cautery dehorning. The NSAIDs investigated have pharmacokinetic properties in cattle that produce persistent plasma concentrations that may provide prolonged analgesia with the added practicality of a simple administration regimen. One hundred and eighty-five Holstein calves aged approximately 50 d old were either sham dehorned (n = 31) or cautery dehorned following oral administration of carprofen (n = 31), firocoxib (n = 31), flunixin meglumine (n = 30), meloxicam (n = 31) or placebo (n = 31) in a randomized, controlled trial. A standard dose of 2.0 mg/kg was administered to all calves receiving an oral NSAID. All calves received local anesthesia prior to actual or sham dehorning. Cortisol concentrations, heart rate, mechanical nociception thresholds, ocular and dehorning area temperatures, and average daily gains were evaluated. A linear mixed-effects model with repeated measures was used for statistical analysis. Administration of oral meloxicam, flunixin meglumine, and firocoxib at 2.0 mg/kg resulted in decreased cortisol concentrations compared to placebo-treated controls for the first 24 h postdehorning (AUEC(0–24)) (P = 0.03). Moreover, firocoxib, flunixin meglumine, and meloxicam attenuated the maximum cortisol concentrations compared to placebo-treated calves (P = 0.04, P= 0.02). In calves treated with flunixin meglumine, cortisol concentrations was reduced at 4 h (P = 0.04) and 8 h (P = 0.02). In addition, analgesic administration was associated with changes in ocular and dehorning area temperature differences (P = 0.09). Carprofen and meloxicam reduced heart rates during the entire study period (P = 0.003). Although a treatment effect (P < 0.0001) was observed in the determination of mechanical nociception threshold among all treatment groups, meloxicam expressed marginally significant effects (P = 0.09) among NSAID treated groups dehorned. A single dose of oral meloxicam, flunixin meglumine, or firocoxib administered at 2.0 mg/kg reduced the acute stress response associated with cautery dehorning. However, carprofen administration was associated with increased cortisol concentrations and dehorning area temperatures for the initial 24 h. Given the changes in pain and stress outcome variables assessed in this study, NSAIDs should be administered at the time of dehorning.